Communicative genological analysis in practice on the example of research on TV news - Siekiera, Rafał (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The analysis of selected TV news services presented in this chapter illustrates the implementation of some of the assumptions of communicative genological analysis. The author focuses on the characteristics of news services as a genological scenario, defining its typical components - the circumstances of its creation, the arrangement of its structure, script participants, signals triggering the scenario (recognized by the recipient and influencing his interpretive attitude with regard to genre interpretation). Individual elements are presented in the form of sequences of predicate-argument systems - in accordance with the assumptions of communicativism, this is how standard scenarios, which are part of linguistic and social competence, can be written.